Lung Ultrasound in the Early Diagnosis and Management of the Mild Form of Meconium Aspiration Syndrome: A Case Report - Alessandro Perri; Simona Fattore; Giorgia Prontera; Maria Letizia Patti; Annamaria Sbordone; Milena Tana; Vito D’Andrea; Giovanni Vento (Diagnostics, 2023)
MAS is a common cause of neonatal respiratory distress in term and post-term neonates. Meconium staining of the amniotic fluid occurs in about 10–13% of normal pregnancies, and about 4% of these infants develop respiratory distress. In the past, MAS was diagnosed mainly on the basis of history, clinical symptoms, and chest radiography. Several authors have addressed the ultrasonographic assessment of the most common respiratory patterns in neonates. In particular, MAS is characterised by a heterogeneous alveolointerstitial syndrome, subpleural abnormalities with multiple lung consolidations, characterised by a hepatisation aspect. We present six cases of infants with a clinical history of meconium-stained fluid who presented with respiratory distress at birth. Lung ultrasound allowed the diagnosis of MAS in all the studied cases, despite the mild clinical picture. All children had the same ultrasound pattern with diffuse and coalescing B-lines, pleural line anomalies, air bronchograms, and subpleural consolidations with irregular shapes. These patterns were distributed in different areas of the lungs. These signs are specific enough to distinguish between MAS and other causes of neonatal respiratory distress, allowing the clinician to optimise therapeutic management.